JUMLAH TIKUS TERTANGKAP MENGGUNAKAN UMPAN IKAN ASIN, KELAPA BAKAR, DAN GORENGAN: (Studi Di Terminal Kalimas Pelabuhan Tanjung Perak Surabaya) - Mas Adhi Hardian Utama; Suhartono; Budiyono (Gema Lingkungan Kesehatan, 2023)
Mechanical rat control usually uses traps, and bait is an important factor in successful rat catching. The aim of this study was to describe the diversity of species and sex of rats, as well as to measure the differences in the effectiveness of using salted fish, roastedcoconut and fried foods on the number of rats caught at Kalimas Terminal, Tanjung Perak Port, Surabaya.This research is a quasi-experimental research with a Posttest Only Design research design and was conducted at Kalimas Terminal, Tanjung Perak Port, Surabaya. The variables in this study were the type of bait used, namely salted fish, grilled and fried coconut and the number of rats caught. The tools used were 150 single live traps, each of which 50 traps were baited with salted fish, roasted coconut and fried foods. The ratscaught were identified for their type, sex and number. Species and sex were analyzed using a frequency distribution table, then an ANOVA test with α of 5% was used to analyze differences in the number of rats based on the type of bait installed.The rat species caught were Rattus norvegicus with 57 individuals (15 males and 42 females) and Rattus tanezumi 17 individuals (6 males and 11 females). The number of rats that entered the trap using salted fish bait was 41 tails, 18 rats used roasted coconut bait, and 15 rats used fried bait. There is a difference in the use of salted fish, roasted coconut and fried food on the number of rats caught at the Kalimas Port of Tanjung Perak, Surabaya(p-value = 0.001).Salted fish is the most effective bait compared to roasted and fried coconut. Its use can be replaced with fried bait periodically if the trap success drops drastically.